Fetal proteinuria in diagnosis of congenital nephrosis detected by raised alpha-fetoprotein in maternal serum. - Thom, H (1977)
High concentrations of alpha-fetoprotein (alpha-FP) were found at 14, 19, and 21 weeks gestation in the serum of a woman with a history of unexplained fetal death in her previous pregnancies. The alpha-FP concentration of the liquor also was high at 21 weeks and the pregnancy was terminated. Though the fetus was macroscopically normal, measurement of albumin, alpha-FP, IgG, and alpha2-macroglobulin in the fetal urine showed a selective proteinuria, and congenital nephrosis was diagnosed after examination of the fetal kidneys by electron microscopy. Possibly some fetuses reported to be "false-positive for neural tube defect" may have had renal lesions of this nature. Examination of fetal urine may be the simplest initial diagnostic procedure in any future case.